Parental participation in Post-Pandemic education financing 2023 - Abdul Canter Sangaji; Masduki Ahmad (Enrichment : Journal of Management, 2023)
This journal wants to discuss parental discussions on children's education costs during a pandemic and post-pandemic in 2023. This research uses a qualitative method and in-depth interviews with all sources. This study found three perspectives, the first is the perspective of education administrators, the second is the person in charge of education, the third is parents. The state of the pandemic at that time could be classified as a state of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA). No one could predict the end of the pandemic at that time, family financial problems occurred because there were layoffs, termination of employment, termination of employment, and those who tried to sell them did not do some of these things which caused problems with financing education. After the pandemic, the majority of families have improved their economic situation, but there are some parents who are still having problems in the financial sector. The purpose of this research is to take a close look at how school crisis management works, how parents survive during a crisis, and how they can get out of financial problems, we found some of these things in this research. The purpose of this research is to become knowledge material for education providers so they can be better prepared to face uncertain conditions during a pandemic.